THE EFFECT OF FINANCIAL LITERACY AND FINANCIAL TECHNOLOGY ON MICRO-BUSINESS PERFORMANCE MEDIATED BY FINANCIAL INCLUSION (CASE STUDY OF MICRO-BUSINESSES IN MUARA BULIAN DISTRICT) - Hesti Nila Kusumardiyani; Rike Setiawati; Besse Wediawati; Uswatun Hasanah (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2023)
This study aims to the Effect of Financial Literacy and Financial Technology on business performance through Financial Inclusion mediation in the subdistrict Muara Bulian. This research is quantitative and the research data used are primary and secondary. The sample is in the subdistrict Muara Bulian, totalling 93 actors. Data collection was carried out by distributing questionnaires with a Likert scale. Data testing techniques use the Validity Test and Reliability Test, R-Square test and Hypothesis Test with Bootstrapping using SmartPLS 3.0 Software. The results showed that Financial Literacy had a positive significant effect on Business Performance, Financial Technology had a positive significant effect on Business Performance, Financial Literacy had a positive significant effect on Financial Inclusion, Financial Technology had a positive significant effect on Financial Inclusion, Financial Inclusion had a positive significant effect on Bussiness Performance, Financial Literacy had a positive significant effect on Business Performance with Financial Inclusion mediation, Financial Technology had a positive significant effect on Business Performance with Financial Inclusion mediation.